EFEKTIFITAS PENERAPAN KEGIATAN TAHFIDZ QUR’AN DALAM PEMBENTUKAN KARAKTER SISWA MI AL-ISHLAH PONDOK PESANTREN TULUNGAGUNG - Ulvia, Ulvia Fatkurin Fuad; Retno Intan Kuswari (STAI KH. Muhammad Ali Shodiq, 2023)
This research is motivated by the phenomenon of a learning process in schools that experience learning difficulties, especially in Al-Qur'an learning which can shape students' character to be better. The focus of this research is: 1) How is the planning for the application of tahfidz Qur'an activities for the formation of student character at MI Al-Ishlah Islamic Boarding School on the Tulungagung stage? 2) What are the effects of tahfidz Qur'an activities in forming the character of students at MI Al-shlah Islamic boarding school stage. This research is qualitative research and the type of research used is case study. Data collection is done by collecting data through observation, interviews and documentation techniques. Data analysis techniques use data reduction, data exposure and drawing conclusions and data verification. What will happen from this research is: 1) The tahfidz program implemented at MI Al-Ishlah is carried out during extracurricular hours by memorizing juz 30 and special surahs, at the age of 6 years. 2) the application or results of the application of tahfidz Qur'an activities in the process of character formation including: a) consequences outside of tahfidz activities such as diligent prayer in congregation and diligent muroja'ah of the Qur'an, b) consequences within tahfidz Qur'an activities such as mastering reading and reciting Al-Qur'an verses and being orderly in participating in tahfidz Qur'an activities.